Solubility Enhancement of Resveratrol by Formulation of Solid Lipid Nanoparticles - Aundhia, Chintan (Asian Journal of Pharmaceutics (AJP), 2024)
Resveratrol is a stilbenoid, a type of natural phenol, and a phytoalexin produced by several plants such as grapes, blueberries, raspberries, mulberries, and peanuts with poor water solubility. The concept of reducing the particle size to nano dimensions was used to improve its solubility. Resveratrol-loaded solid lipid nanoparticles (SLNs) were developed using stearic acid as the lipid and poly vinyl alcohol (PVA) as the stabilizing agent. Resveratrol-loaded SLN were prepared using solvent evaporation technique and concentration of stearic acid and PVA were taken as the variables for optimization. Entrapment efficiency (EE) and yield of the SLN were taken as the dependent variables. All the responses observed for 13 formulations prepared were simultaneously fitted to linear, 2F1, quadratic, and cubic models using Design-Expert 10. It was observed that the best-fitted model was response surface, a quadratic model. SLN were characterized for yield, EE, particle size, zeta potential, and surface morphology. In vitro drug release studies were performed in phosphate buffer of pH 6.8 using dialysis bag diffusion technique. It was observed that in the case of SLN, the solubility was obtained approximately 3 times more than pure drug.